Bargaining for pay equity: an NZ-inspired approach to gender equality in Australia. (3rd July 2021) - Pennington, Alison; Wenlock, Megan
ABSTRACT: Women's disproportionate representation in insecure, low-paid, or unpaid care work presents persistent barriers to women's capacity to work and earn. The COVID-19 pandemic has intensified these barriers to adequately paid, sufficient-hours work. Consequently, women earn almost one-third less than men across all jobs. The industrial system is a critical mechanism for weeding out structural pay discrimination from wage structures. However, Australia's system for pursuing pay equity is stumbling due to the absence of bargaining infrastructure required to test and enforce pay equity legislation. In Aotearoa New Zealand (NZ), new laws have been introduced facilitating bargaining-led solutions to gendered pay discrimination. Parallel implementation of a bold new system of sectoral bargaining called 'Fair Pay Agreements' in 2022 will allow reformed pay equity and collective bargaining systems to co-articulate. Inspired by these developments in NZ, CPSU Victoria has negotiated new gender equality measures in the Victorian public sector (VPS) agreement. While limited to the public sector, the VPS Agreement provides a powerful example of innovative industrial approaches to pursuing gender equity. A NZ-inspired bargaining approach to gender equity can boost women's wages, reduce inequality, and revitalise a labour regime fit-for-purpose in the modern, feminised service economy.